A CONSTRUÇÃO DE UMA PONTE:LINGUAGEM, REFERENCIAÇÃO, SUBJETIVIDADE E IDENTIDADE - Martins, Waldiney Corrêa (2016)
Adopting an interactional conception of language, of subject and text, the aim of this study is to observe the strategies of introduction (construction) and resumption (reconstruction) of textual referents (speech objects), in three Official Letters of the nineteenth century, from the city of Castro. I emphasize that these three letters were written by the same subject and show, as theme, the construction of the Jaguaricatu River‟s bridge. Comparing to the physical construction of the bridge, that obviously needs two poles to be built, I consider that language, referencing, subjectivity and identity are also kinds of "bridge", as they need the "other" – another subject – to be manifested. I emphasize that the analysis is done by tracking referential sequences, according to the methodology adopted by Roncarati (2010). I highlight the introduction and resumption of referents, disregarding those which are mentioned just one time. At the same time speech objects are identified, I show how the subjectivity and identity are presented by referencing, as the subject makes choices to attend its communication purposes. These choices can be stylistic marks of social roles, revealing the identities of the subjects. With regard to language, I base on the postulations of Bakhtin‟s group. For referencing, I have Mondada e Dubois (2003), Koch (2008), Koch e Elias (2006, 2009), Marcuschi (2007), among others. With regard to the subjectivity, I have Moita Lopes (1998), Bakhtin (2000). Regarding to identity, I have Hall (1999), Woodward (2000) and Bauman (1998). And about discursive genres, I have relied on Bakhtin (2000) and Bazerman (2006), among other authors that contribute to the study.